EFFECTS OF SUPPLEMENTING MOLASSES VIA DRINKING WATER ON LAMBS PERFORMANCE AND CARCASS CHARACTERISTICS - D. A. O. Al-Sherwany; A. A. Hussein (مجلة الأنبار للعلوم الزراعية)
Fifteen Turkish Karayaka lambs of similar live weights (LW) 36±4.62 kg were placed in three groups of 5 each and fed similar diets. The drinking water of the T1 and T2 groups was supplemented with molasses (Mo) at 50 and 100ml/5Lwater/lamb, respectively, while Mo was not provided to the control group lambs (C). Three lambs per group were slaughtered to study carcass characteristics. Daily total DMI in C, T1, and T2 were almost the same at 1.75, 171, and 1.77 kg/d, respectively. Final and daily LW gains were not affected (P>0.05) by Mo supplementation although T2 and T1 lambs had numerically higher LWs at 4.8 and 1.6 kg, respectively. Differences were not observed (P>0.05) between treatments in shrinkage, rib eye area, fat thickness, and dressing percentage based on LW and empty BW. Adding Mo resulted in an increase in slaughter weight by 5.6 and 8.6 kg in T1 and T2, respectively compared to C. Similarly, lambs in the T1 group yielded a numerically higher (P>0.05) dressing percentage based on body weight (51.71%) than those in C (49.31%). There was no effect (P>0.05) of Mo on all wholesale cuts and offal organs except shoulder cuts and lungs trachea which were lower (P<0.05) in the treated groups compared to C. Lambs in C had numerically higher lean percentages than the Mo-supplemented groups though fat value was lower. The Mo supplementation numerically increased lambs LBW due to higher body fat at the expense of lean mass